Diversity of nitrogen assimilation pathways among microbial photosynthetic eukaryotes. Issue 3 (6th April 2015) - Terrado, Ramon; Monier, Adam; Edgar, Robyn; Lovejoy, Connie; Mock, T.
<x xml:space="preserve">Abstract</x> In an effort to better understand the diversity of genes coding for nitrogen (N) uptake and assimilation pathways among microalgae, we analyzed the transcriptomes of five phylogenetically diverse single celled algae originally isolated from the same high arctic marine region. The five photosynthetic flagellates (a pelagophyte, dictyochophyte, chrysoph‐yte, cryptophyte and haptophyte) were grown on standard media and media with only urea or nitrate as a nitrogen source; cells were harvested during late exponential growth. Based on homolog protein sequences, transcriptomes of each alga were interrogated to retrieve genes potentially associated with nitrogen uptake and utilization pathways. We further investigated the phylogeny of poorly characterized genes and gene families that were identified. While the phylogeny of the active urea transporter (DUR3) was taxonomically coherent, those for the urea transporter superfamily, putative nitrilases and amidases indicated complex evolutionary histories, and preliminary evidence for horizontal gene transfers. All five algae expressed genes for ammonium assimilation and all but the chrysophyte expressed genes involved in nitrate utilization and the urea cycle. Among the four algae with nitrate transporter transcripts, we detected lower expression levels in three of these (the dictyochophyte, pelagophyte, and cryptophyte) grown in the urea only medium compared with cultures from the nitrate only media. The diversity of N pathway genes in the five algae, and their ability to grow using urea as a nitrogen source, suggest that these flagellates are able to use a variety of organic nitrogen sources, which would be an advantage in an inorganic nitrogen ‐ limited environment, such as the Arctic Ocean.